Analysis of Nathaniel Character in the Film Entitled ‘Enchanted’ by Kevin Lima: Analysis of Nathaniel Character in the Film Entitled ‘Enchanted’ by Kevin Lima - Garwan, Hellaisna Nur'Aini (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Abstract Nathaniel is one of peripheral characters in the movie entitled ‘Enchanted’. In the beginning of the movie, he was the antagonist one. He is the accomplish of Queen Narissa. Nathaniel experienced a moment that open his eyes so that he against Queen Narissa. The change of Nathaniel’s character drew researcher’s attention so that she was interested in discussing his character. The purpose of this research is to identify and to find out inner conflict which influences Nathaniel’s actions and thoughts later in the movie ‘Enchanted’. Researcher used library research to analyze this film. Structural approach was used by researcher in order to collect data as well. Researcher found out that Nathaniel had interesting personality. He was so in love with Queen Narissa so he would anything for her. Nathaniel was also good at disguise and could adapt in totally different environment. His character was very different from the main character. Even though in the beginning of the movie Nathaniel was described as antagonist, in the end of the movie he changed his thought and defensed for the main character. That move showed everyone had good side in his/her heart. People can change over time. Keywords: character, film ‘Enchanted’, Nathaniel.